(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2019)
Tungsten is one of the hardest metals that has high melting point and high thermal conductivity. These unique properties make it suitable for many industrial applications. The increasing demand for using tungsten made the need for a fast and reliable analytical technique for tungsten to increase. In this paper we are comparing the ability of LIBS as a multi-elemental analysis technique to PIXE which is a well known established multi-elemental technique in the analysis of tungsten alloys. It was found that LIBS has the advantage over PIXE in the detection of the trace and minor elements. While PIXE is better than LIBS in the detection of major elements in the samples.